Microsoft Dynamics AX 2009 development cookbook : solve real-world Dynamics AX development problems with over 60 simple but incredibly effective recipes /: solve real-world Dynamics AX development problems with over 60 simple but incredibly effective recipes. (2009) - Unknown
No abstract available